Multi-level short-term forecasting of the total electrical load of the power pool system - Chernenko, P. A.; Martyniuk, A. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
This paper deals with the brief description of the technique of multilevel multivariate short-term prediction of total electrical loads (TEL) of energy enterprise and detailed algorithm for solving this problem by using the information, available in power systems of Ukraine, regarding the factors, influencing variations of TEL.